Traceability model system as originality assurance method for honey product, Indonesia - Jaisy Aghniarahim Putritamara; Rahmi Yuniarti; Anie Eka Kusumastuti (Journal of Social Studies (JSS), 2021)
Honey is a hype product as immunity booster in the health shock covid-19. Unbalance of supply and demand has raised the price and made the consumer could not afford it. Besides that, global issue about unoriginal honey which spreads in society has made the consumer has negative stigma on SMEs honey product because it does not have complete food safety certification as commercial company. Objective of the research was to increase the consumer trust through originality assurance for honey product from traceability system. The research is a case study with FGD method and then followed by Interpretive Structural Modeling (ISM) analysis and Business Process Notation as solution. Result of the research showed that the distribution aspect has great power to affect the stakeholder and logistic aspects, due to success of both aspects are determined by distribution aspect. While the stakeholder aspect does not have any power to affect other aspect because if the business system has correct SOP, then both aspects will have appropriate supply chain management. Therefore, the solution is business process improvisation, so that to increase the trust local brand for honey product, it must be optimized through recording system of customer journey, so that the producer could trace the barrier and enabler factors about perspective of the honey originality